2007
DOI: 10.1158/0008-5472.can-07-0780
|View full text |Cite
|
Sign up to set email alerts
|

Control of Ocular Tumor Growth and Metastatic Spread by Soluble and Membrane Fas Ligand

Abstract: Fas ligand (FasL) can be either membrane bound, or cleaved by metalloproteinases (MMP) to produce a soluble protein.The two different forms of FasL are reported to have opposite functions-membrane-bound FasL (mFasL) is proinflammatory and soluble FasL (sFasL) is antiinflammatory. We previously showed that, within the immune-privileged eye, tumors expressing high levels of mFasL overcame the suppressive ocular environment, triggered an inflammatory response, and were subsequently rejected. By contrast, eye tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The molecular mechanisms of metastasis remain incompletely understood. TNF superfamily proteins, including TRAIL, have been proposed to be involved in the metastases of some tumors (17,18,25,26). Our present study demonstrates that MIL6 cells derived from a metastatic lesion were markedly resistant to TRAIL exposure, while MIT6 cells from the primary tissues were considerably sensitive (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…The molecular mechanisms of metastasis remain incompletely understood. TNF superfamily proteins, including TRAIL, have been proposed to be involved in the metastases of some tumors (17,18,25,26). Our present study demonstrates that MIL6 cells derived from a metastatic lesion were markedly resistant to TRAIL exposure, while MIT6 cells from the primary tissues were considerably sensitive (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, studies show that membrane-bound and soluble (as a result of cleavage by metalloproteinases) FasL have the opposing effects. While membrane FasL is pro-inflammatory, soluble FasL is antiinflammatory [17,18]. We showed here that soluble FasL was a positive regulator of angiogenesis in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, there is a Previous studies reported that Fas, commonly regarded as an inducer of cell apoptosis, may induce inflammatory angiogenesis [6,16,17]. In murine model where Matrigel was used as a vehicle for the delivery of agonistic anti-Fas antibody Jo2, there were no apoptotic cells detected in the process of angiogenesis, suggesting it may be mediated by stimulatory signal through Fas-engagement [6].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that FasL engagement of Fas ϩ macrophages not only induces apoptosis but also induces the production of neutrophil chemotactic factors (14). Moreover, using an ocular tumor model, we demonstrated that overexpression of the membrane form of FasL within the immune-privileged eye induced a potent neutrophil-mediated inflammatory response, leading to the termination of ocular immune privilege (15,16). Together, these studies suggest that a more efficient and/or rapid engagement of the Fas receptor on cells resident within the eye will trigger a quicker innate-mediated inflammatory response, accelerate pathogen clearance, and ultimately increase resistance to bacterial endophthalmitis.…”
mentioning
confidence: 83%